Study of the Effect of Heat Treatments on the Ability of Flat Springs to Resist Permanent Deformation - علي سليمان; هترة علي; سعيد علي (Latakia University Journal -Engineering Sciences Series, 2021)
The effect of heat treatment on the resistance of SUP3 flat springs to permanent deformation was studied. The heat treatments produced different microstructures that gave the steel different mechanical properties, and to evaluate the properties we conducted different tests on the specimen followed by preparing a mathematical model for a flat spring that was loaded with a small load. It was found that the Isothermal treatment resulted in an increase of yield strength and this led to an increase in the material’s resistance to permanent deformation compared to other specimens.